Some Effects of Participative Budgeting on Managerial Behavior. - Barden, Ronald S. (The Accounting Review, 1975)
Reviews the book "Some Effects of Participative Budgeting on Managerial Behavior," by Robert J. Swieringa and Robert H. Moncur.